Comparative analysis of chloroplast genomes for five Dicliptera species (Acanthaceae): molecular structure, phylogenetic relationships, and adaptive evolution - Sunan Huang; Xuejun Ge; Asunción Cano; Betty Gaby Millán Salazar; Yunfei Deng (PeerJ, 2020)
The genus Dicliptera (Justicieae, Acanthaceae) consists of approximately 150 species distributed throughout the tropical and subtropical regions of the world. Newly obtained chloroplast genomes (cp genomes) are reported for five species of Dilciptera (D. acuminata, D. peruviana, D. montana, D. ruiziana and D. mucronata) in this study. These cp genomes have circular structures of 150,689–150,811 bp and exhibit quadripartite organizations made up of a large single copy region (LSC, 82,796–82,919 bp), a small single copy region (SSC, 17,084–17,092 bp), and a pair of inverted repeat regions (IRs, 25,401–25,408 bp). Guanine-Cytosine (GC) content makes up 37.9%–38.0% of the total content. The complete cp genomes contain 114 unique genes, including 80 protein-coding genes, 30 transfer RNA (tRNA) genes, and four ribosomal RNA (rRNA) genes. Comparative analyses of nucleotide variability (Pi) reveal the five most variable regions (trnY-GUA-trnE-UUC, trnG-GCC, psbZ-trnG-GCC, petN-psbM, and rps4-trnL-UUA), which may be used as molecular markers in future taxonomic identification and phylogenetic analyses of Dicliptera. A total of 55-58 simple sequence repeats (SSRs) and 229 long repeats were identified in the cp genomes of the five Dicliptera species. Phylogenetic analysis identified a close relationship between D. ruiziana and D. montana, followed by D. acuminata, D. peruviana, and D. mucronata. Evolutionary analysis of orthologous protein-coding genes within the family Acanthaceae revealed only one gene, ycf15, to be under positive selection, which may contribute to future studies of its adaptive evolution. The completed genomes are useful for future research on species identification, phylogenetic relationships, and the adaptive evolution of the Dicliptera species.